Blended Learning with the SDGs Life on Land–Based Forest Keeper Game to Develop Ecological Awareness of Pre-Service Elementary Teachers - Hana lestari; Ima Rahmawati; Novi Yanthi; Alifa Ferhani (Jurnal Ilmiah Sekolah Dasar, 2026)
Ecological awareness among prospective teachers remains suboptimal, particularly in bridging the gap between environmental knowledge and pro-environmental behavior. This study aims to examine the effectiveness of blended learning integrated with the Forest Guardian game in enhancing ecological awareness among prospective primary school teachers. The study employed a quantitative approach using a pre-experimental one-group pre-test and post-test design. The participants consisted of 155 students enrolled in an Environmental Education course. Data were collected using a 30-item ecological awareness questionnaire covering environmental knowledge, attitudes, and pro-environmental behavior, as well as an observation sheet to assess the implementation of learning activities. Data were analyzed using descriptive statistics and a paired sample t-test. The results indicate a significant improvement in students’ ecological awareness, with the mean score increasing from 59.5 in the pre-test to 83.5 in the post-test. The paired sample t-test revealed a significance value of p = 0.01 (p < 0.05), confirming the effectiveness of the intervention. The findings suggest that integrating face-to-face instruction, online learning, and game-based experiential activities fosters active engagement and meaningful understanding of environmental issues. This study implies that blended, simulation-supported learning can serve as an effective pedagogical approach to strengthen sustainability competencies in teacher education.